KONSEP PESERTA DIDIK DALAM ALQURAN DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM ERA DIGITAL - Neng Nurcahyati Neng (Pascasarjana UIN Sumatera Utara, 2023)
Education is a direction or guidance given to students, which is adjusted to their physical and spiritual development towards the stage of maturation. Essentially, the concept of Islamic education in the digital era can never be separated from the role of an educator who truly gives all his knowledge so that students can develop their morals well, and that is of course based on the guidance of the Qur'an and Hadis. With regard to the topics discussed, this research is classified as literature research, in which all data processing is analyzed interactively, and is supported by a variety of accurate educational literature. As for in this study, there are several findings, namely (1) students in the Koran occupy the most important position in Islamic education, namely not only subjects but objects in the implementation of the development of Islamic education in the digital era, (2) characteristics of students in the perspective of Islamic education in the digital era including, have a sanctity of soul, are not arrogant towards knowledge, respect educators, have independence in learning, discipline, and have responsibilities as a student, (3) further discussion regarding the concept of students and their implications for Islamic education in the digital era is basically always related to the development of materials, curriculum and development of other teaching materials that make students continue to hone their knowledge, especially in the field of Islamic education.